Penerapan Literasi Keuangan Dalam Menumbuhkan Minat Berwirausaha - Hesty T. Salle; Westim Ratang; Paulus K. Allo Layuk; Agustinus Salle; Klara Wonar; Gabriel Yusuf; Marcelinus A. Salle; Yeperson Narek; Elsyan R. Marlissa; Vince Tebay; Ilham Ilham (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Currently, many young people are trying to start a business either independently or join an existing business. With the increasingly developing digital era, it is very easy to do many things, including by starting your own business. Because the business carried out does not require large capital and a place to open a business. Currently, efforts can be made through social media such as TikTok, Facebook, Instagram and other social media. These media are currently widely used by young people to start a business. However, often new businesses fail in a short time due to the lack of beginner entrepreneurs' knowledge related to financial literacy. Lack of financial literacy can lead to poor calculations in business and also worsen personal financial conditions, as budding entrepreneurs cannot separate finances for business and personal. The purpose of this PKM is to provide an understanding of financial literacy in fostering the interest of youth and adolescents in starting entrepreneurship and the use of digital media to become content creators, especially in the Youth Service (Pelprap) of GPI Eben-Haezer Kotaraja. This method of community service starts from pre-test, material delivery, interactive discussions, and conducting promotional practices through TikTok accounts. The results of this PkM show that the understanding of financial literacy and interest in entrepreneurship has increased, as evidenced by the results of the post test with a result of 73%.